2005
DOI: 10.1115/1.2168475
|View full text |Cite
|
Sign up to set email alerts
|

Bond Graph Based Approach to Passive Teleoperation of a Hydraulic Backhoe

Abstract: Human operated, hydraulic actuated machines are widely used in many high-power applications. Improving productivity, safety and task quality (eg. haptic feedback in a teleoperated scenario) has been the focus of past research. For robotic systems that interact with the physical environments, passivity is a useful property for ensuring safety and interaction stability. While passivity is a well utilized concept in electromechanical robotic systems, investigation of electrohydraulic control systems that enforce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A comparison of the Bond Graph method with object oriented modeling is done by Borutzky (2002), where it was found that both methods can be equally reliable, if they are used in appropriate applications and effectively implemented. The basics of bond graph based control and substructuring are analyzed by Gawthorp et al (2009), while Krishnaswamy and Li (2006) used the Bond Graph method in the passive teleoperation of a hydraulic backhoe. Additional work in the field of bond graph modeling of nonlinear hydro-mechanical systems has been conducted by Margolis and Shim (2005), while Li and Ngwempo (2005) have used bond graph modeling in electro-hydraulic valves.…”
Section: Ajasmentioning
confidence: 99%
“…A comparison of the Bond Graph method with object oriented modeling is done by Borutzky (2002), where it was found that both methods can be equally reliable, if they are used in appropriate applications and effectively implemented. The basics of bond graph based control and substructuring are analyzed by Gawthorp et al (2009), while Krishnaswamy and Li (2006) used the Bond Graph method in the passive teleoperation of a hydraulic backhoe. Additional work in the field of bond graph modeling of nonlinear hydro-mechanical systems has been conducted by Margolis and Shim (2005), while Li and Ngwempo (2005) have used bond graph modeling in electro-hydraulic valves.…”
Section: Ajasmentioning
confidence: 99%
“…Recent work has also focused on stability of a remote haptic feedback system, as evidenced by literature [6][7][8][9][10][11][12][13], much of which has focused on passivity control. Significant amount of work has also focused on making the teleoperation system transparent to the user, including, as described by the work of Flemmer, Lawrence, and Zhu in [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Suitable controllers are defined to achieve passivity with respect to a desired supply rate. A bond graph based controller for bilateral tele-operation is presented in [4]. In both [4] and [8], the actuator energy is defined based on linear models and the compressibility of actuator is not modeled.…”
Section: Introductionmentioning
confidence: 99%
“…A bond graph based controller for bilateral tele-operation is presented in [4]. In both [4] and [8], the actuator energy is defined based on linear models and the compressibility of actuator is not modeled. In [7], an energy function based on the nonlinear dynamics of the actuator is presented.…”
Section: Introductionmentioning
confidence: 99%